A numerical method for the solution of singular and singularly perturbed boundary value problems - Tadi, Mohsen; Radenkovic, Miloje; Wang, Yuanlong (International Journal of Applied Mathematical Research, 2014)
This note is concerned with a new numerical method for the solution of singular and singularly perturbed boundary value problems. The method uses Fourier sine series and is suitable for Dirichlet-type boundary value problems. It removes the singularity of the problem in a natural way. A number of numerical examples are used to study the applicability of the method. Keywords: Dirichlet-type boundary valueproblems, Singular boundary value problems, Singularly perturbed baoundary value problems.